2021
DOI: 10.18332/tid/143027
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting smoking initiation and cessation among adult smokers in Fiji: A qualitative study

Abstract: INTRODUCTION Smoking as a public health challenge is globally considered the main risk factor of many non-communicable diseases (NCDs). Knowing factors contributing to smoking commencement and cessation is the necessary step to develop prevention strategies to combat this issue. To date, no study has been conducted in Fiji, therefore this study aimed to explore the reasons adult smokers initiate smoking and cessation in Fiji. METHODS A qualitative study was conducted am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 39 publications
0
2
1
Order By: Relevance
“…Thus, it is significant that we were able to interview and describe the need for smoking cessation based on smoking experiences. These points in the present study differ from those in existing qualitative studies with narratives from smokers [31][32][33][34][35]. Further, this need was identified not only toward professionals but also toward their peers and society.…”
Section: Discussioncontrasting
confidence: 97%
See 1 more Smart Citation
“…Thus, it is significant that we were able to interview and describe the need for smoking cessation based on smoking experiences. These points in the present study differ from those in existing qualitative studies with narratives from smokers [31][32][33][34][35]. Further, this need was identified not only toward professionals but also toward their peers and society.…”
Section: Discussioncontrasting
confidence: 97%
“…When chronic symptoms and behavior occur, it is necessary to consider the behavior in the context of the entire life of the parties involved in the process [30]. In recent qualitative studies, individuals who smoked were asked directly about their smoking behavior, socio-cultural and environmental factors influencing smoking [31], perspectives on smoking habits [32], factors affecting smoking initiation and cessation [33], reasons for failure to quit smoking [34], and experiences of attempts to quit smoking [35]. However, the results of each study were based on the cultural background and living environment of the country or region and are expected to differ between countries or regions.…”
Section: Introductionmentioning
confidence: 99%
“…A study conducted among Norwegian adults reported that higher education significantly predicts smoking cessation [ 45 ]. Another qualitative enquiry from Fiji reported that knowledge on harms of smoking was among the factors influencing smoking cessation [ 46 ]. Evidence from India indicates that a smoker’s education level is correlated with positive attitude towards smoking cessation and quit attempts [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Efforts to stop smoking and successful quitting among tobacco users are also predicted by the motivation to quit, which could be influenced by cultural factors 15 . Studies show that religious reasons have positively spurred university students to stop smoking 16 .…”
Section: Introductionmentioning
confidence: 99%